Effect of microwave heating on accelerated ageing qualities of rice - Nayak, Mana; Mohapatra, Minati (ORYZA-An International Journal of Rice, 2019)
The effect of microwave heating (MWH) i.e. microwave power (540, 720, 900 W)(MWP) and exposure time (30, 60, 90 s)(ET) at a constant moisture content of 12.4±1.8 % wb of the paddy on milling and ageing properties i.e. total yield, head rice yield (HRY), cooking time, kernel elongation ratio (KER), volume expansion ratio (VER), water uptake, solid loss, gel consistency, hardness and stickiness was evaluated. These properties were determined for microwave treated and compared with freshly harvested rice and naturally aged paddy samples of 6 months storage. Head rice yield was maximum 50.67±0.17 % in microwave treated sample whereas it was 38.0 ±0.37 % in freshly harvested rice sample. Higher exposure time (90 s) and microwave power (720, 900 W) yielded lower head rice (41.50±0.42 and 43.74±0.14 %) may be due to rapid interaction of water molecules to electromagnetic field to internal fissure development of grains which caused high moisture gradient and strain in kernel and lead to more broken kernels. The cooking time of freshly harvested rice (control sample) was less (17.0± 1.52 min) compared to microwave heating at 900 W for 60 s (25.2± 0.50 min) and 6 month naturally aged rice (27.0±0.80 min). KER of cooked rice was higher (2.87 ± 0.23) for 900 W MWP and 60s ET and VER for this case was achieved more than 3±0.37. Solid loss was less and Water uptake of rice during cooking was more towards higher exposure time i.e. 90 s and 900 W and 540 W power. The water uptake and GC values gave more or less similar results showing no definite trend. Water uptake was more in microwave treated rice i.e. 81.0±0.79 % than freshly harvested rice (65.0± 1.08 %) and six months naturally aged rice (73.00± 1.5 %). The freshlyharvested rice gave a softer gel consistency (38.20± 1.18 mm), whereas, MWH rice gave harder gel (GC 25.90±0.92 mm) as that of 6 months stored rice of GC 27.50± 1.15 mm. Considering all these properties, microwave treatmentof rice at 900 W MWP and 60 s ET has achieved better ageing qualities i.e. more cooking time, KER, VER, water uptake, harness of grain and less solid loss, gel consistency and stickiness of rice.